Associations among vascular risk factors, neuroimaging biomarkers, and cognition: Preliminary analyses from the Multi‐Ethnic Study of Atherosclerosis (MESA). Issue 4 (5th September 2021) - Lockhart, Samuel N.; Schaich, Christopher L.; Craft, Suzanne; Sachs, Bonnie C.; Rapp, Stephen R.; Jung, Youngkyoo; Whitlow, Christopher T.; Solingapuram Sai, Kiran Kumar; Cleveland, Maryjo; Williams, Benjamin J.; Burke, Gregory L.; Bertoni, Alain; et al.
Abstract: Introduction: Little is known about how antecedent vascular risk factor (VRF) profiles impact late‐life brain health. Methods: We examined baseline VRFs, and cognitive testing and neuroimaging measures (β‐amyloid [Aβ] PET, MRI) in a diverse longitudinal cohort (N = 159; 50% African‐American, 50% White) from Wake Forest's Multi‐Ethnic Study of Atherosclerosis Core. Results: African‐Americans exhibited greater baseline Cardiovascular Risk Factors, Aging, and Incidence of Dementia (CAIDE), Framingham stroke risk profile (FSRP), and atherosclerotic cardiovascular disease risk estimate (ASCVD) scores than Whites. We observed no significant racial differences in Aβ positivity, cortical thickness, or white matter hyperintensity (WMH) volume. Higher baseline VRF scores were associated with lower cortical thickness and greater WMH volume, and FSRP and CAIDE were associated with Aβ. Aβ was cross‐sectionally associated with cognition, and all imaging biomarkers were associated with greater 6‐year cognitive decline. Discussion: Results suggest the convergence of multiple vascular and Alzheimer's processes underlying neurodegeneration and cognitive decline.